PEMBANGUNAN M-BEKAM BERBASIS SISTEM PAKAR - Rendra Gustriansyah; Hastha Sunardi; Nazori Suhandi (UNIVERSITAS INDO GLOBAL MANDIRI)
Cupping is a detoxification therapy or methods of treatment by removing oxidants from the body through certain points on the surface of the epidermis. Currently, in Western countries (Europe and America) conducted scientific research seriously and continuously to reveal the scientific facts, how the magic of cupping to cure various diseases more safely and effectively than the methods of modern medicine. This is the consideration for making an expert system cupping method. This expert system uses backward chaining method to determine the points of cupping treatment which is implemented on a mobile device based on Android, so this application has the potential to be accessed anytime and anywhere by experts bruise or community. The use of expert systems on cupping method is expected to solve the problem of health according to the knowledge base that are known by experts bruise and also in accordance with the Sunnah of the Prophet Muhammad SAW.